1992
DOI: 10.1111/j.1365-2826.1992.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids are Required for Food Deprivation‐Induced Increases in Hypothalamic Neuropeptide Y Expression

Abstract: Neuropeptide Y (NPY), a 36 amino-acid peptide found within the hypothalamus, is thought to be an important regulator of food intake. Hypothalamic NPY gene expression, synthesis and secretion are all known to be increased in models of increased metabolic demand in which serum glucocorticoids are also elevated. The present studies were designed to test the hypothesis that glucocorticoids are required for increased hypothalamic preproNPY mRNA levels induced by food deprivation (FD). First, animals underwent bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 58 publications
4
24
1
Order By: Relevance
“…Previous reports have suggested that elevated plasma corticosterone may be necessary for fasting-induced increase in NPY mRNA expression. 20,21 However, in this study, NPY expression in the arcuate nucleus of MS pups was not increased by 24 h food deprivation on PND 29 despite the significant elevation of plasma corticosterone, in contrast to the NH pups showing fasting-induced increases not only of the plasma corticosterone but also of the arcuate NPY. Thus, it is suggested that elevated plasma corticosterone, although it may be necessary, may not be sufficient to increase the arcuate NPY expression during food deprivation.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Previous reports have suggested that elevated plasma corticosterone may be necessary for fasting-induced increase in NPY mRNA expression. 20,21 However, in this study, NPY expression in the arcuate nucleus of MS pups was not increased by 24 h food deprivation on PND 29 despite the significant elevation of plasma corticosterone, in contrast to the NH pups showing fasting-induced increases not only of the plasma corticosterone but also of the arcuate NPY. Thus, it is suggested that elevated plasma corticosterone, although it may be necessary, may not be sufficient to increase the arcuate NPY expression during food deprivation.…”
Section: Discussioncontrasting
confidence: 64%
“…It has been suggested that plasma corticosterone is implicated in the hypothalamic NPY expression. [18][19][20][21] Taken together, it is concluded that a chronic increase in plasma corticosterone in MS/RF rats during the repeated fasting/RF cycles might have contributed to a tonic increase in NPY expression, and the increased plasma corticosterone and NPY expression by repeated fasting/RF cycles may partly be in charge of the sustained compensatory hyperphagia in the MS/RF group. Previous reports have suggested that elevated plasma corticosterone may be necessary for fasting-induced increase in NPY mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in circulating corticosterone and decrease in leptin during food deprivation has been suggested to correlate with fasting-induced changes in the hypothalamic feeding peptides expression. That is, elevated plasma corticosterone was necessary for fasting-induced increase of NPY mRNA expression in mice (Ponsalle et al, 1992;Makimura et al, 2003); the hypothalamic POMC expression has been suggested to be regulated by glucocorticoids (Cintra and Bortolotti, 1992;Savontaus et al, 2002) and leptin (Korner et al, 1999;Schwartz et al, 2000), and the hypothalamic CART by leptin (Kristensen et al, 1998;Lambert et al, 1998). In this study, a 48 h of food deprivation did not significantly increase mRNA level of NPY, nor decrease POMC and CART, in the arcuate nucleus of NH females, despite of a significant increase in the plasma corticosterone and a decrease in leptin.…”
Section: Discussionmentioning
confidence: 99%
“…The arcuate nucleus could also be the site for glucocorticoid action, because glucocorticoid receptor (GR) is expressed in the NPY neurons (Hisano et al, 1988), and peripheral as well as central injection of glucocorticoids increased the NPY expression (Wilding et al, 1993;Zakrzewska et al, 1999). More importantly, NPY gene expression was not increased by insulin deficiency if rats were adrenalectomized (Ponsalle et al, 1992;Strack et al, 1995). These data suggest that insulin and glucocorticoids interact with each other to regulate NPY gene expression, although the exact sites of the interaction are not clear.…”
Section: Introductionmentioning
confidence: 71%